Searching for alumni Faculty of Sports Science Universitas Negeri Yogyakarta as a relevant study efforts - Guntur, Guntur; Sumaryanto, Sumaryanto; Siswantoyo, Siswantoyo; Alim, Abdul; Utami, Nur Sita (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2021)
This study aims to determine the level of FIK UNY alumni in the world of work. This study uses a quantitative descriptive research approach with a survey method. The sample of this research is FIK UNY alumni in the 2016-2020 graduate year. The sampling technique was carried out incidentally so that 353 respondents were collected. The data collection technique used in this research is a questionnaire. The instrument used is a questionnaire which is presented online through the website tracer.uny.ac.id and google form. Analysis of the data used in this study using quantitative description analysis techniques. Alumni get a job before graduation as much as 30.88%, after graduation 40.51%, and 28.61% not looking for work. Alumni who are not looking for work are generally the reason for continuing their Master’s studies or PPG (Professional Teacher Program) studies.